The Influence of Leadership, Organizational Commitment, and Work Environment on Employee Performance - Ismansyah, Defrino; Parwoto, Parwoto (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This study aims to determine the effect of leadership, organizational commitment and work environment on employee performance at PT Sugity Creatives Indonesia. The research method is associative research, with data collection through a questionnaire, literature study and interviews. Testing was carried out with a sample of 64 people using the purposive sampling method, measurement scales using Likert scale. On the analysis of data using multiple linear regression test with SPSS 26 program.Testing of partial variable results that showed leadership affected the employee performance with a level of significance of 0.007 < 0.05. organizational commitment has no effect on employee performance with a level of significance of 0.110> 0.05, and work environment affects employee performance with a level of significance of 0.032< 0.05. Therefore, it needs to be a serious concern for leaders in PT Sugity Creatives Indonesia affecting the performance of the employees, of some of the indicators that the author described based on a detailed questionnaire results are expected to increasingly see the performance of employees in PT Sugity Creatives Indonesia.